Pengelolaan dan Pengembangan Wakaf Uang oleh Lembaga Nazhir di Kota Pekanbaru - Nuryanti, Nuryanti; Lubis, Haniah; Cheumar, Muhammad Tahir; Melina, Ficha (AL-Muqayyad, 2024)
The existing cash waqf assets are not yet fully managed by nazhir, because in the Pekanbaru City area there are still limited nazhir resources to manage waqf, both in terms of quality and quantity. This research seeks to explain the management of cash waqf assets and how to develop waqf management by cash waqf nazhir institutions in Pekanbaru City so that the potential of cash waqf can be explored. The research carried out was descriptive qualitative field research. Data was obtained by interviewing informants, namely 6 nazhir cash waqf institutions in Pekanbaru City. Data is presented descriptively based on conditions that occur in the field. The management of cash waqf that has been carried out by nazhir cash waqf institutions in Pekanbaru City has not shown maximum results considering the huge potential. However, the efforts made by these institutions show their seriousness in managing cash waqf. Various programs have been prepared to develop the management of cash waqf in order to increase the benefits of waqf that can be distributed to mauquf 'alaih.The main contribution of this research is to focus on managerial techniques in managing cash waqf in Pekanbaru City.